Glacial and Holocene terrestrial temperature variability in subtropical east Australia as inferred from branched GDGT distributions in a sediment core from Lake McKenzie. Issue 1 (July 2014) - Woltering, Martijn; Atahan, Pia; Grice, Kliti; Heijnis, Henk; Taffs, Kathryn; Dodson, John
Abstract: Branched glycerol dialkyl glycerol tetraether (GDGT) distributions observed in a sediment core from Lake McKenzie were utilized to quantitatively reconstruct the pattern of mean annual air temperature (MAAT) from coastal subtropical eastern Australia between 37 and 18.3 cal ka BP and 14.0 cal ka BP to present. Both the reconstructed trend and amplitude of MAAT changes from the top of the sediment core were nearly identical to a local instrumental MAAT record from Fraser Island, providing confidence that in this sediment core branched GDGTs could be used to produce a quantitative record of past MAAT. The reconstructed trend of MAAT during 37 to 18.3 cal ka BP and timing of the Last Glacial Maximum (LGM) in the Lake McKenzie record were in agreement with previously published nearby marine climate records. The amplitude of lower-than-present MAAT during the LGM potentially provides information on the latitude of separation of the Tasman Front from the East Australian current in the subtropical western Pacific. The Lake McKenzie record shows an earlier onset of near modern day warm temperatures in the early Holocene compared to marine records and the presence of a warmer than present day period during the mid-Holocene.